Acid attack performance of 3D printing Nano-ZnO modified geopolymer mortar - Gardezi, Syed Shujaa Safdar; Tanyildizi, Harun; Haroglu, Hasan; Coskun, Ahmet (Elsevier, 2025)
The current study investigated the acid attack resistance of 3D-printed geopolymer mortars that contained nano zinc oxide (nano-ZnO) with varying content of 0 %, 0.25 %, 0.5 %, and 0.75 %, respectively. The mortars were produced using Metakaolin (MK) and fly ash (FA). Fresh properties of samples were assessed by determining viscosity, setting time, flowability, and buildability. For hardened properties, samples with dimensions 40 x 40 x 160 mm were prepared and cured for a period of 28 days at a temperature of 20 +/- 2 degrees C. To observe the impact of acid attack, the samples were subjected to 5 % Hydrochloric acid (HCl) for 28 days. After that, the variations in weight, compressive strength, and flexural strength of samples were evaluated. Furthermore, X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray (EDX) helped to observe the microstructure of 3D-printed geopolymer mortar samples. It has been found that nano-ZnO has a considerable impact on the fresh properties. Whilst the buildability was enhanced with the increased content of nano-ZnO, flowability was adversely affected due to the increased stiffness. It is also observed that compressive and flexural strength have been positively impacted in an acidic environment by the increased content of nano-ZnO. The highest flexural and compressive strength values were obtained in samples containing 0.5 nano-ZnO. When the 0.5 % nano-ZnO sample exposed to acid was compared with the reference (0 % nano-ZnO) sample, a 33.64 % and 42.86 % increase in compressive and flexural strength was observed. Results from this study demonstrated that the use of nano-ZnO in geopolymer composites could reduce the acid attack.
Keywords: 3D printed geopolymer mortar; Nano-zinc oxide; Acid environments; Fresh properties; Hardened properties